Only in theaters [videorecording (DVD)] - Engman, Isabelle; Garcia, Gerardo (Kino Lorber, 2023)
There has been a Laemmle in the movie business since there's been a movie business. This is the story of a beloved Arthouse Cinema chain in Los Angeles with an astounding legacy. Over four generations, Laemmle's have dedicated themselves to supporting, innovating, and elevating the art of filmmaking. Popularizing independent films, documentary films, and their filmmakers, the LaemmleTheatres' impact on Hollywood and world cinema cannot be overstated. The Laemmle family is determined to keep their business and legacy alive, but in a changing world, the future of cinema is uncertain.